1989
DOI: 10.1155/1989/528758
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous Gastritis

Abstract: A 54-year-old woman presented with nausea, vomiting and weight loss associated with impaired gastric emptying necessitating institution of parenteral nutrition. Subsequent studies revealed an unusual gastric mucosa! inflammatory nrocess characterized by unique subepithelial collagenous deposits. Collagenous gastritis appears to be a distinct, possibly immune-mediated, chronic disorder, pathologically reminiscent of collagenous sprue and collagenous colitis.Can J Gastroenterol 1989;3(5): [171][172][173][174] Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 1 publication
2
15
0
Order By: Relevance
“…[17][18][19] The patient with collagenous gastritis reported here also had topographic mapping and electron microscopic studies of gastric mucosal biopsies with results previously reported elsewhere. 19…”
Section: Diagnosis Of Lymphocytic and Collagenous Gastritissupporting
confidence: 73%
“…[17][18][19] The patient with collagenous gastritis reported here also had topographic mapping and electron microscopic studies of gastric mucosal biopsies with results previously reported elsewhere. 19…”
Section: Diagnosis Of Lymphocytic and Collagenous Gastritissupporting
confidence: 73%
“…1,2 To date, B50 patients with collagenous gastritis have been reported in the English language literature, mainly as reports of one or two cases. [3][4][5][6][7][8][9][10][11][12][13][14][15] The two largest previous series comprised 6 and 12 patients, respectively. 16,17 On the basis of patient age and clinical presentation, Lagorce-Pages et al 16 recognized two general clinical subgroups in collagenous gastritis.…”
mentioning
confidence: 99%
“…Collagenous gastritis is an extremely rare clinicopathological entity, with 20 cases reported in the English literature to date from the United States, Germany, Canada, France, Spain, India, Japan, and Korea [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Collagenous gastritis is a rare disorder, with 20 cases reported in the English literature to date [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]; the pathogenesis and prognosis remain unknown. Collagenous gastritis is defined histologically by the presence of a subepithelial collagen band thicker than 10 µm in association with increased inflammatory cell infiltrate of the lamina propria [9] and it is therefore straightforward to make a histological diagnosis from a biopsy specimen.…”
Section: Introductionmentioning
confidence: 99%